Unraveling The Link: Relationship Firm Value Shapes Esg Ratings - Priyanto, Panji; Suhandi, Ni Putu Mila (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
The study aims to fill the research gap by examining the relationship between ESG ratings and firm value in energy companies and whether company profitability controls this relationship. The study uses multiple regression models to test this hypothesis and examines the impact of Tobin's Q, profitability, and ESG ratings on firm value. The study sample is energy sector companies listed on the Indonesia Stock Exchange from 2015-2022. The result of this paper is a negative relationship between Tobin's Q and ESG performance, indicating that firms with higher market valuations may prioritize shareholder value over ESG considerations. On the other hand, there is a positive relationship between NPM and ESG performance, suggesting that companies with higher profitability may have more resources to invest in sustainable and socially responsible practices. The lack of a significant relationship between ROE and ESG performance suggests that the financial returns to equity shareholders may not directly impact on a company's ESG initiatives. The positive relationship between ROA and ESG Performance aligns with the idea that companies with efficient asset utilization are better positioned to invest in sustainable practices. The negative relationship between GPM and ESG Performance suggests that companies with higher gross profit margins may face pressure to cut costs, potentially at the expense of environmental or social responsibility.